Kali Linux wireless penetration testing : master wireless testing techniques to survey and attack wireless networks with Kali Linux : beginner's guide /: master wireless testing techniques to survey and attack wireless networks with Kali Linux : beginner's guide. (2015) - Ramachandran, Vivek; Buchanan, Cameron
No abstract available